Crisis of «the little person» in stories «Melancholy» of A. P. Chekhov and «Wedding and Funeral» Muhammad Teymur (comparative analysis) - Валид Ахмед, Толба (Journal of Oriental Studies, 2017)
Interest of the Egyptian literature in works of the Russian writers and especially to A. Chekhov’s creativity was not casual. Universality and versatility of the sphere of search in universal and humane questions pushed the Egyptian writers to be interested in masterpieces of the Russian writers. And not only coincidence in historical and public conditions connected his creativity with Arab, but also a form of the small story corresponding to liking the Arab mentality., therefore in works of the Egyptian short-story writer hatred to oppression, injustice, and stratification of society is always felt.